Penerapan Metode Storytelling dalam Meningkatkan Keterampilan Berbicara Teks Negosiasi Siswa Kelas X SMAN 3 Sinjai - Nur Ilham Mahsya Salman; Sitti Rabiah; Nurfathana Mazhud (Departement of Mathematics Education, 2024)
This study aims to determine the effectiveness of the application of storytelling methods to students' speaking skills in learning negotiation texts in class X3 SMAN 3 Sinjai. Research conducted With a total of 30 students and using a classroom action research approach carried out in 2 cycles. The instruments used in this study were observation sheets to measure student activity and speaking skills tests to measure students' speaking skills in negotiation text learning. The results showed that the application of the storytelling method effectively improved students' speaking skills which was characterized by an increase in the percentage of student completeness in speaking skills i.e. from 70% in cycle I to 90% in cycle II. Student activity during the learning process also increased from 81.66% in cycle I to 84.66% in cycle II. This proves that students become more motivated and enthusiastic during negotiation text learning by applying the storytelling method. Based on the results of this study, it can be concluded that the application of the storytelling method in learning negotiation texts is proven effective for improving students' speaking skills. Students become more confident and skilled when speaking and negotiating after being taught through storytelling methods. This method is recommended to be applied to other classes that want to improve students' speaking skills. Schools also need to facilitate training for teachers to master the application of innovative learning methods such as storytelling.